Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.biochem.0c00766
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Roles of Two Histidine Residues in Streptococcus pyogenes Cas9 Catalytic Domains upon Chemical Rescue

Abstract: CRISPR-Cas9 technology has been at the forefront of the field of biology. The Streptococcus pyogenes (SpyCas9) protein forms a complex with guide RNA and can recognize and cleave double-stranded DNA through hybridization based on 20 base pairings. SpyCas9 has two nuclease domains, HNH and RuvC, each of which cuts each DNA strand, and both contain critical histidine residues. Although previously reported crystal structures provide useful geometric information, the extent to which these residues functionally con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(44 reference statements)
1
5
1
Order By: Relevance
“…This data was different from the studies of Furuhata et al. (the basicity) and Krishnan et al (introduction of IMs to Michael acceptor). , In addition, although the long distance between the IM and QM was shown, our study indicated that introduction of IMs might promote the Michael addition of CEL. Interestingly, a similar phenomenon also appeared in another Michael acceptor, CDDO, and its derivatives, which indicated that the strategy might be applicable to more Michael addition receptors …”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This data was different from the studies of Furuhata et al. (the basicity) and Krishnan et al (introduction of IMs to Michael acceptor). , In addition, although the long distance between the IM and QM was shown, our study indicated that introduction of IMs might promote the Michael addition of CEL. Interestingly, a similar phenomenon also appeared in another Michael acceptor, CDDO, and its derivatives, which indicated that the strategy might be applicable to more Michael addition receptors …”
Section: Resultscontrasting
confidence: 99%
“…16−18 Interestingly, the previous study reported that the catalytic activity of SpyCas9 histidine mutants can be restored by the addition of imidazoles and substituted imidazoles (IMs). 18 Moreover, Krishnan et al found that the covalent binding between acrylonitrile (a Michael acceptor) and thiol could be enhanced once an aromatic heterocycle (such as imidazole, triazole, pyridine, etc.) was introduced as an electronwithdrawing group to the Michael acceptor.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target DNA strand complementary to spacer RNA was cut by the HNH nuclease domain and the non-target DNA strand by the RuvC nuclease domain to produce a blunt-ended double-strand breakage at 3 bp upstream to PAM [63,64]. Either D 10 A [58] or H 983 A [65] mutation destroyed the RuvC nuclease activity. On the other hand, D 839 A [66], H 840 A [58], and N 863 A [67] mutations could eliminate the HNH nuclease activity.…”
Section: Crispr/cas Nucleasesmentioning
confidence: 99%
“…For instance, Cas9 recognizes the PAM sequence NGG found directly downstream of the target DNA on the non-target strand (ANDERS et al, 2014). The cleaving properties of the RNA-guided endonucleases lie on two catalytic domains: HNH and RuvC, each cutting a DNA strand (FURUHATA; KATO, 2021). The CRISPR-Cas system goes as far as creating the DSBs in a targeted and precise manner.…”
Section: The Crispr-cas System and Cas Variationsmentioning
confidence: 99%